Pengadaan Vaksin Covid-19 Triwulan I Tahun 2021 di Indonesia Persfektif Hukum Ekonomi Syariah - Kuryani Saputra; A. Kumedi Jafar; Muhammad Iqbal Fasa (LPPM Institut Nasional Laa Roiba Bogor, 2022)
In the first quarter of 2021, Indonesia will purchase vaccines by importing COVID-19 vaccines from COVID-19 vaccine companies. Islamic Economic Law regulates the process of purchasing vaccines by importing Covid-19 vaccines, how transactions are completed, and aspects of the safety and halalness of Covid-19 vaccines. The purpose of this study was to determine the import contract of Indonesia's Covid-19 vaccine with halal guarantees and health aspects in accordance with sharia economic law. This research uses literature study method. The data analysis method used in this research is deductive analysis. The data collection method in this research is documentation. Sources of data used are primary and secondary data sources. The main data sources used in this study are COVID-19 vaccines, vaccine books, import and export of Islamic law and economics, Islamic law, trade law, and documents related to precedents contained in Islamic law. Sources of supporting data used in this research come from scientific studies, articles, and books that support the research topic. From the perspective of Islamic economic law, the purchase of the Covid-19 vaccine in Indonesia is included in the Salam sale and purchase contract. MUI has announced that the Covid-19 vaccine product is halal and multifaceted. In accordance with Presidential Regulation No. 99 regarding vaccine procurement and vaccination implementation in 2020, the current sales contract is in effect. For the Covid-19 pandemic, if there is a mandatory threat, the contract can be extended. Or cancel. The government guarantees the safety, type and quality of halal products as well as the effectiveness of the Covid-19 vaccine (namely the POM and MUI). The type of covid-19 vaccine with guaranteed halal products and an emergency use license is the type of vaccine from PT. Bio Farma (Persero), Sinovach Biontech Ltd, AstraZeneca.Keywords : vaccine procurement, covid-19 vaccine, salam contract